Implementation of the #HouseProject Program as a Community-Based Tourism Application in Bantarkaret Tourism Village Bogor - Hasna, Andra Sahirah; Ridanti, Cut Fairi Auni; Etania, Dita Listya; Ardiyatna, Kadek Ayu Maharani (Kontibusi: Jurnal Kontribusi Kepada Masyarakat, 2023)
One strategy to keep the tourism industry alive during the pandemic is to promote it through social media. The COVID-19 pandemic in Indonesia has impacted many things, including travel trends, where tourist destinations and attractions will focus more on the concept of Nature, Eco, Wellness, and Adventure (NEWA). A tourist destination that has this concept is a tourism village. One of the tourism villages that is categorized as a developing village is Bantarkaret Village. Bantarkaret Tourism Village aims to involve the community as tourism agents and administrators as a way of implementing community based tourism, which is a characteristic of a tourism village. This program focuses on giving photography, social media, and tourism planning training to the Bantarkaret Tourism Village local community in increasing competitiveness and productivity, and also preparing the community for the new normal era. The implementation of this program is guided by information processing theory and the stages of the tourism planning process model.